The impact of cooking and burial on proteins: a characterisation of experimental foodcrusts and ceramics - Evans, Miranda; Hagan, Richard; Bondetti, Manon; Boyd, Oliver; Craig, Oliver E; Collins, Matthew J; Hendy, Jessica (The Royal Society, 2024)
Foodcrusts have received relatively little attention in the burgeoning field of proteomic analysis of ancient cuisine. We remain ignorant of how cooking and burial impact protein survival, and crucially, the extent to which the extractome reflects the composition of input ingredients. Therefore, through experimental analogues we explore the extent of protein survival in unburied and buried foodcrusts and ceramics using ‘typical’ Mesolithic ingredients (red deer, Atlantic salmon and sweet chestnut). We then explore a number of physicochemical properties theorised to aid protein preservation. The results reveal that proteins were much more likely to be detected in foodcrusts than ceramics using the methodology employed, input ingredient strongly influences protein preservation, and that degradation is not universal nor linear between proteins, indicating that multiple protein physicochemical properties are at play. While certain properties such as hydrophobicity apparently aid protein preservation, none single-handedly explain why particular proteins/peptides survive in buried foodcrusts: this complex interplay requires further investigation. The findings demonstrate that proteins indicative of the input ingredient can be identifiable in foodcrust, but that the full proteome is unlikely to preserve. While this shows promise for the survival of proteins in archaeological foodcrust, further research is needed to accurately interpret foodcrust extractomes. This project has received funding from the European Union's EU Framework Programme for Research and Innovation Horizon 2020 under Grant Agreement No. 722606: TEMPERA. This work was supported by the Cambridge Trust and Newnham College through an international studentship awarded to M.E. and a Philip Leverhulme Prize awarded to J.H. We thank the ERC Advanced Grant INDUCE (The Innovation, Dispersal and Use of Ceramics in NE Europe, ERC-ADG-2015 Number 695539), which funded the creation of experimental samples.